(untitled) (Религиски дијалог и соработка, 2025)
The paper explores the popularity of spiritual movements that draw on Eastern energy concepts: Ki in the case of Reiki and Tantric ideas about erotic energy in Western groups inspired by Tantrism. The focus is also on their opponents and critics, especially in the second case study.